Multimodality imaging assessment of primary pericardial rhabdomyosarcoma: a case report - Li, Xingxuan; Cao, Yukun; Shao, Guozhu; Cui, Yue; Li, Yumin; Zhang, Kailu; Liu, Xiaoqing; Shi, Heshui (Frontiers in Cardiovascular Medicine, 2023)
Primary pericardial sarcomas are rare and lethal diseases. To date, only a few cases of primary pericardial sarcomas, such as rhabdomyosarcoma (RMS), have been reported. Since the unusual location of RMS in the pericardium makes it challenging to diagnose, precise diagnostic procedures are required. In this study, we present the case of a 23-year-old man who experienced postprandial obstruction and atypical precordial pain that lasted for a week. Echocardiography revealed a heterogeneous isoechoic pericardial mass with a significant pericardial effusion. Contrast-enhanced CT revealed a massive pericardial effusion along with an irregular, defined, heterogeneously enhancing mass that was located between the pericardium and diaphragm. PET-CT imaging showed an intense FDG uptake in the pericardial mass. Furthermore, cardiac MRI demonstrated malignant characteristics of the pericardial mass and provided a detailed visualization of its exact anatomical connection with both cardiac and extracardiac structures. Finally, a pathologic examination of a puncture biopsy specimen confirmed the diagnosis of primary pericardial RMS. Our case emphasizes the importance of multimodal imaging for the differential diagnosis and evaluation of cardiac involvement, while providing clinicians with crucial information for clinical treatment and decision-making.